Physical Functioning and Mortality among Individuals with Type 2 Diabetes: Insights from TRIAD - Ylitalo, Kelly R. (J Diabetes Complications, 2013)
Diabetes is a risk factor for mortality. Subjective health status, including self-reported physical functioning, may also be a marker for mortality. This study examined the association between self-reported physical functioning and mortality in people with diabetes, and determined if this association differed by race/ethnicity. We studied 7,894 type 2 diabetic patients who participated in Translating Research Into Action for Diabetes (TRIAD), a prospective study of diabetes care in managed care. At baseline in 2000, participants completed a questionnaire and had a medical record review. Physical functioning was assessed with the Short Form Health Survey (SF-12). The National Death Index was searched annually for deaths over 10 years of follow-up (2000-2009). At baseline, mean age was 61.7 years, 50% were non-Hispanic white, 22% were black, and 16% of participants reported “good physical functioning” (better than norms for U.S. adults). Over 10 years, 28% of participants died (2,111/7,894); 39% (856/2,111) due to cardiovascular disease. Relative to those reporting good functioning, those reporting poor physical functioning had a 37% higher all-cause death rate, after adjusting for age, sex, race/ethnicity, education, income, body mass index, smoking, and comorbidities (Hazard Ratio (HR)=1.37; 95% Confidence Interval (CI): 1.15, 1.63). Similarly, those reporting poor physical functioning had a 42% higher adjusted cardiovascular death rate compared to those reporting good functioning (HR= 1.42; 95% CI: 1.06, 1.90). Although blacks were less likely than whites to report good functioning (p<0.01), the association between functioning and mortality was consistent across race/ethnicity. In this managed care population with diabetes, self-reported physical functioning was a robust predictor of mortality, in addition to traditional biological risk factors, for all race/ethnic groups. Physical functioning assessments are easy to perform and may be useful benchmarks for tailoring the care of persons with chronic disease.